Projected uptake of sulfadoxine–pyrimethamine for perennial malaria chemoprevention in children under 2 years of age in nine sub-Saharan African countries: an epidemiologically-based 5-year forecast analysis - Céline Audibert; Pierre Hugo; Roly Gosling; Charlotte Eddis; Meredith Center; André Marie Tchouatieu (Malaria Journal)
Abstract Background Perennial malaria chemoprevention (PMC) with sulfadoxine–pyrimethamine (SP) is recommended for children under 2 years of age living in areas of perennial malaria transmission. Initially delivered through the Expanded Programme of Immunization (EPI), recent pilot studies explored PMC delivery via the vitamin A supplementation programme or community health workers (CHWs). Understanding SP demand across the various delivery channels is key to implementing PMC. Methods A 5-year epidemiologically-based forecasting model was developed to estimate SP volumes required for nine sub-Saharan countries based on seven different scenarios considering the EPI, vitamin A or CHWs delivery channels, alone or in combination. Model inputs were secondary data sources, enhanced with information from a field survey conducted among 40 national decision-makers and 176 healthcare providers. Projected SP volumes were estimated based on expected coverage and uptake within the eligible population. The efficiency of meeting the need versus demand was calculated for each scenario. A sensitivity analysis was performed for base, low and high estimates of the coverage and uptake rates. The forecasting period was 2023 to 2027. Results The eligible population in the study countries was estimated at 21 million children in 2023. Estimated demand in 2027 ranged from 17.8 million SP doses for EPI to 49.6 million when combining all delivery channels. These results were highly dependent on the coverage and uptake rate of each delivery channel. The sensitivity analysis showed that uncertainty around the estimates ranged from twofold (Vitamin A), to 3.4-fold (CHWs). EPI was the most efficient channel overall (53%), but the efficiency of each scenario varied by country depending on local contexts. Conclusions The model provides a tool to anticipate SP needs and demand for PMC under various scenarios, aiding manufacturers, donors, partners, governments, and procurement organizations in effective planning for PMC implementation.